MOTIVASI MASYARAKAT TERHADAP PENANAMAN MAHONI (Swietenia macrophylla) STUDI KASUS DI DESA SUNGAI ENAU KECAMATAN KUALA MANDOR B KABUPATEN KUBU RAYA - Herwina, Dina; AM, Iskandar; muin, sudirman (Universitas Tanjungpura, 2017)
This study aims to assess the level of society motivation for the planting of mahogany (Swietenia macrophylla) in Sungai Enau Village, and assess the relationship between factors that influencing motivation and the level of society motivation on mahogany planting. The factors that affect society motivation are: (1) perception (2) knowledge (3) income, and (4) land area, so that to increase the income of the society from the economic side as well as doing a short-term or long-term of greening program in order to reduce deforestation in Kubu Raya Regency. This Study uses descriptive analysis and inferential analysis, and using Kendall Tau correlation test which each of them given the weight of score and the result of observation data in the form likert scale quantized. The result of this study indicate that the society motivation on mahogany has moderat motivation level with frequency as much as 38 (76%), and there is no significant correlation between factors which influencing motivation with society motivation level on the planting of mahogany in Sungai Enau Village, Sub-district Kuala Mandor B Kubu Raya Regency.Keywords: Likert Scale, Mahogany Planting, Society Motivation